Keberkesanan Modul Kaunseling Pemulihan Terhadap Masalah Psikososial Orang Kurang Upaya (Oku) Fizikal Akibat Kemalangan - Husain, Zuhda (2014)
This study is a combined between quantitative and qualitative research aimed at developing and determining the effectiveness of Rehabilitation Counseling Module on the psychosocial problems of people with physical disabilities (PWD) caused by accidents. Apart from that, this study also sought to identify the psychosocial problems experienced by the physically disabled people due to accidents. A total of 11 subjects were involved in this study. The subjects were given a pre and posttest by applying 48 ICET survey questions. In addition, the subjects were also required to answer interview questions before and after the rehabilitation counseling sessions. For the purpose of data analysis, Wilcoxon T test was used to identify differences in the mean score of the pre and posttest before and after rehabilitation counseling sessions. The findings show that there are differences in the mean of psychosocial problems towards the needs of support services with the significance of .007. The analysis of interview and documentation find that there is a positive changes to the subjects in their psychosocial problems, in term of psychology and relationship such as stress, depression, emotional disturbance, acceptance, adjustment, social interactions and relationship with normal environment before joining the rehabilitation counseling sessions.